Psychoemotional disorders in patients with rheumatoid arthritis: research results - Nikolenko Алла (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". Eighty women, patients with RА in the age of from 16 till 60 years (average age 42,4±1,18), with duration of disease from 1 year till 30 years (average duration 8,36±0,79) were surveyed. The borderline mental disorders of patients with RА were investigated. Experimental psychological inspection was carried out with use of techniques: ТАS (Toronto Alexithymia Scale ), BIPQ (Bechterev Institute personal questionnaire), Teilor’s Manifest Anxiety Scale.